Retardation films and polarizing plates

JP7633011B2Active Publication Date: 2025-02-19NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020146964
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-01
Publication Date
2025-02-19
Estimated Expiration
2040-09-01

AI Technical Summary

Benefits of technology

【0006】 本発明の実施形態によれば、特定のポリカーボネート系樹脂を含み、突刺し弾性率を特定の範囲内とすることで、搬送中の工程不良の発生が抑制され、さらに屈曲性に優れた位相差フィルムを実現することができる。さらに、単位膜厚あたりの突刺し強度、破断強度および破断伸度を特定の範囲内とすることで、フィルムの押し込みの際の輝点の発生が抑制され、耐皮脂性および耐クラック性に優れた位相差フィルムを実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633011000001
    Figure 0007633011000001
  • Figure 0007633011000002
    Figure 0007633011000002
  • Figure 0007633011000003
    Figure 0007633011000003
Patent Text Reader

Abstract

To provide a retardation film which suppresses the occurrence of process defects while being conveyed and generation of bright spots when the film is pressed in, is less susceptible of whitening and / or cracking, and offers superior flexibility and sebum resistance.SOLUTION: A retardation film provided herein contains a specific polycarbonate resin, exhibits an in-plane retardation Re (550) in a range of 200-400 nm, a ratio Re (450) / Re (550) in a range of 0.98-1.03, and a puncture modulus of 50 gf / mm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a retardation film and a polarizing plate. [Background technology]

[0002] In recent years, with the spread of thin displays, image display devices (organic EL display devices) equipped with organic EL panels have been proposed. Organic EL panels have a highly reflective metal layer, and are prone to problems such as external light reflection and background reflection. It is known that these problems can be prevented by providing a retardation film on the viewing side. However, with conventional retardation films, process defects such as folds, wrinkles, and dents may occur during film transport, and bright spots may occur when the film is pressed. Furthermore, when conventional retardation films are used on the viewing side of image display devices, whitening and / or cracks may occur with use, and further bending and sebum resistance may be insufficient. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and an object of the present invention is to provide a retardation film that suppresses the occurrence of process defects during transportation, suppresses the occurrence of bright spots when the film is pressed, suppresses the occurrence of whitening and / or cracks, and further has excellent flexibility and sebum resistance. [Means for solving the problem]

[0005] The retardation film in the embodiment of the present invention contains a polycarbonate resin, has an in-plane retardation Re(550) of 200 nm to 400 nm, Re(450) / Re(550) of 0.98 to 1.03, and a puncture modulus of 50 gf / mm or more. In one embodiment, the retardation film has a puncture strength per unit thickness of 10 gf / μm or more. In one embodiment, the retardation film has a breaking strength of 800 MPa or more. In one embodiment, the retardation film has a thickness of 30 μm to 50 μm. In one embodiment, the variation in Re(550) of the retardation film in the width direction is 5 nm or less. In one embodiment, the retardation film has an absolute value of a rate of change in in-plane retardation Re(550) after 500 hours under conditions of a temperature of 65° C. and a humidity of 90%, of 3% or less. In one embodiment, the moisture permeability of the retardation film is 100 g / m 2 Less than 24 hours. In one embodiment, the retardation film has a breaking elongation of 4% or more. In another embodiment of the present invention, there is provided a polarizing plate with a retardation layer. The polarizing plate with a retardation layer includes a polarizer and the above-mentioned retardation film attached to at least one surface of the polarizer via an adhesive layer. Effect of the Invention

[0006] According to an embodiment of the present invention, by containing a specific polycarbonate-based resin and setting the puncture modulus within a specific range, the occurrence of process defects during transportation can be suppressed, and a retardation film with excellent flexibility can be realized. Furthermore, by setting the puncture strength, breaking strength, and breaking elongation per unit film thickness within specific ranges, the occurrence of bright spots when the film is pressed can be suppressed, and a retardation film with excellent sebum resistance and crack resistance can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0008] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film).

[0009] A. Retardation film The retardation film according to the embodiment of the present invention contains a polycarbonate resin, and is typically a stretched film of a polycarbonate resin film.

[0010] The retardation film has an in-plane retardation Re(550) of 200 nm to 400 nm, preferably 220 nm to 380 nm, and more preferably 240 nm to 360 nm. That is, the retardation film can function as a λ / 2 retardation plate.

[0011] The retardation film exhibits flat wavelength dispersion characteristics in which the retardation value hardly changes depending on the wavelength of the measurement light. The retardation film has Re(450) / Re(550) of 0.98 to 1.03, preferably 0.99 to 1.03, and more preferably 1.00 to 1.03. By using a polycarbonate resin having such Re(450) / Re(550), excellent antireflection characteristics can be realized.

[0012] The puncture elastic modulus of the retardation film is 50 gf / mm or more, preferably 100 gf / mm or more, more preferably 150 gf / mm or more. The puncture elastic modulus is obtained by dividing the force (gf) just before the film breaks (or tears) when a needle (puncture tool) is punctured perpendicularly to the main surface of the film by the strain (mm) at that time. When the retardation film has the above-mentioned puncture elastic modulus, the occurrence of process defects during transportation is suppressed, and a retardation film with excellent flexibility can be obtained.

[0013] The puncture strength per unit thickness of the retardation film is preferably 10 gf / μm or more, more preferably 15 gf / μm or more, and even more preferably 20 gf / μm or more. The puncture strength per unit thickness indicates the strength when the film breaks when a needle is vertically lowered against the film, divided by the thickness. When the retardation film has the puncture strength per unit thickness as described above, the occurrence of bright spots when the film is pressed is suppressed, and a retardation film with excellent sebum resistance can be obtained.

[0014] The rupture strength of the retardation film is preferably 800 MPa or more, more preferably 1500 MPa or more, and even more preferably 2500 MPa or more. The upper limit of the rupture strength of the retardation film may be, for example, 7000 MPa. The rupture strength indicates the stress when the film breaks in a tensile test. When the rupture strength of the retardation film is in such a range, a retardation film having excellent crack resistance can be obtained.

[0015] The retardation film has a breaking elongation of preferably 4% or more, more preferably 5% or more. The upper limit of the breaking elongation of the retardation film may be, for example, 300%. The breaking elongation refers to the strain (elongation rate) at the time when the film breaks after a tensile test is performed after cutting the film. When the breaking elongation of the retardation film is in such a range, a retardation film having excellent crack resistance can be obtained.

[0016] The thickness of the retardation film is preferably 30 μm to 50 μm, and more preferably 35 μm to 45 μm. When the thickness of the retardation film is in such a range, the retardation film can be suitably applied to a thin device.

[0017] The variation of Re(550) in the width direction of the retardation film is preferably 5 nm or less, more preferably 3 nm or less, and even more preferably 2 nm or less. The lower limit of the variation of Re(550) in the width direction of the retardation film can be, for example, 0.5 nm. By defining the variation of Re(550) in such a range, the retardation film can achieve good optical uniformity.

[0018] In the retardation film, the absolute value of the rate of change of the in-plane retardation Re(550) after 500 hours under conditions of a temperature of 65° C. and a humidity of 90% is preferably 3% or less, and more preferably 2% or less. The lower limit of the absolute value of the rate of change may be, for example, 0.01%. The rate of change of the retardation is |(Re 500 -Re0) / Re0|×100(%). Re0 is the in-plane retardation (nm) of the retardation film before the start of the test, and Re 500 is the in-plane retardation (nm) of the retardation film after the test. When the absolute value of the rate of change of the in-plane retardation Re(550) of the retardation film is in such a range, when the retardation film is applied to an image display device, the hue change due to the retardation at each location on the image display device is small, and the occurrence of color unevenness on the display can be suppressed.

[0019] The moisture permeability of the retardation film is preferably 150 g / m 2 - 24h or less, preferably 120g / m 2 24h or less, and more preferably 100g / m 2 The lower limit of the moisture permeability is, for example, 1 g / m 2 If the moisture permeability of the retardation film is within this range, the change in retardation in a humid environment can be suppressed.

[0020] The absolute value of the photoelastic coefficient of the retardation film is preferably 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, and more preferably 1.0×10 -12 m 2 / N~1.2×10 -11 m 2 / N. If the absolute value of the photoelastic coefficient of the retardation film is within this range, the retardation is unlikely to change when shrinkage stress occurs during heating. As a result, when the retardation film is applied to an image display device, the image display device can be effectively prevented from having uneven heat.

[0021] According to the embodiment of the present invention, as described above, a retardation film that satisfies the desired in-plane retardation, wavelength dispersion characteristics and thickness, further suppresses the occurrence of process defects during transportation, suppresses the occurrence of bright spots when the film is pressed, and has excellent flexibility, sebum resistance and crack resistance can be obtained. Such a retardation film can be suitably applied to, for example, notebook personal computers (PCs) and in-vehicle displays.

[0022] B. Constituent materials As described above, the retardation film is typically a stretched polycarbonate resin film.

[0023] (Polycarbonate resin) The polycarbonate resin according to the present invention contains at least a constituent unit derived from a dihydroxy compound having a bonding structure represented by the following structural formula (1), and is produced by reacting a dihydroxy compound containing at least a dihydroxy compound having at least one bonding structure -CH2-O- in the molecule with a carbonate diester in the presence of a polymerization catalyst. [ka]

[0024] Here, as the dihydroxy compound having a bond structure represented by structural formula (1), any compound having two alcoholic hydroxyl groups, a structure having a linking group -CH2-O- in the molecule, and capable of reacting with a carbonic acid diester to produce a polycarbonate in the presence of a polymerization catalyst can be used, and a plurality of compounds may be used in combination. In addition, as the dihydroxy compound used in the polycarbonate resin according to the present invention, a dihydroxy compound not having a bond structure represented by structural formula (1) may be used in combination. Hereinafter, a dihydroxy compound having a bond structure represented by structural formula (1) may be abbreviated as dihydroxy compound (A), and a dihydroxy compound not having a bond structure represented by structural formula (1) may be abbreviated as dihydroxy compound (B).

[0025] (Dihydroxy compound (A)) The "linking group -CH2-O-" in the dihydroxy compound (A) means a structure that bonds with atoms other than hydrogen atoms to form a molecule. In this linking group, as an atom to which at least an oxygen atom can be bonded or an atom to which a carbon atom and an oxygen atom can be bonded simultaneously, a carbon atom is most preferred. The number of "linking groups -CH2-O-" in the dihydroxy compound (A) is preferably 1 or more, more preferably 2 to 4.

[0026] More specifically, examples of the dihydroxy compound (A) include 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, fluorene having an aromatic group in a side chain and bonded to an aromatic group in a main chain, such as 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, and 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene. Compounds with a tertyl group, bis[4-(2-hydroxyethoxy)phenyl]methane, bis[4-(2-hydroxyethoxy)phenyl]diphenylmethane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]ethane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]-1-phenylethane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]propane, 2,2-bis[4-(2-hydroxyethoxy)-3-methylphenyl]propane, 2,2-bis[3,5-dimethyl-4-(2-hydroxyethoxy)phenyl]propane, phenyl]propane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]-3,3,5-trimethylcyclohexane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,4-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,3-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 2,2-bis[4-(2-hydroxyethoxy)-3-phenylphenyl]propane, 2,2-bis[(2-hydroxyethoxy)-3-isopropylphenyl]propane, 2,2-bis[3-tert-butyl-4-(2-hydroxyethoxy)phenyl]propane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]butane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]-4-methylpentane, 2,2-bis[4-(2-hydroxyethoxy)phenyl]octane, 1,1-bis[4-(2-hydroxyethoxy)phenyl]decane, 2,2-bis[3-bromo-4-(2-hydroxyethoxy)phenyl]propane, 2,2-bis[3-cyclohexyl-4-(2-hydroxyethoxy)phenyl] bis(hydroxyalkoxyaryl)alkanes, such as 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclohexane, 1,1-bis[3-cyclohexyl-4-(2-hydroxyethoxy)phenyl]cyclohexane, and 1,1-bis[4-(2-hydroxyethoxy)phenyl]cyclopentane, 4,4'-bis(2-hydroxyethoxy)diphenyl ether, and 4,4'-bis(2-hydroxyethoxy)-3,3'- dihydroxyalkoxy diaryl ethers, such as dimethyl diphenyl ether; bishydroxyalkoxy aryl sulfides, such as 4,4'-bis(2-hydroxyethoxyphenyl) sulfide and 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl] sulfide; bishydroxyalkoxy aryl sulfides, such as 4,4'-bis(2-hydroxyethoxyphenyl) sulfoxide and 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl] sulfoxide; bishydroxyalkoxyarylsulfones, such as 4,4'-bis(2-hydroxyethoxyphenyl)sulfone and 4,4'-bis[4-(2-dihydroxyethoxy)-3-methylphenyl]sulfone, 1,4-bishydroxyethoxybenzene, 1,3-bishydroxyethoxybenzene, 1,2-bishydroxyethoxybenzene, 1,3-bis[2-[4-(2-hydroxyethoxy)phenyl]propyl]benzene, 1,4-bis[2-[4-(2-hydroxyethoxy)phenyl]propyl]benzene, 4,Examples of the compound include anhydrous sugar alcohols such as 4'-bis(2-hydroxyethoxy)biphenyl, 1,3-bis[4-(2-hydroxyethoxy)phenyl]-5,7-dimethyladamantane, dihydroxy compounds represented by the following formula (4), and compounds having a cyclic ether structure such as spiroglycol represented by the following general formula (6). These may be used alone or in combination of two or more kinds.

[0027] [ka]

[0028] These dihydroxy compounds (A) may be used alone or in combination of two or more. In the present invention, the dihydroxy compound represented by the formula (4) includes isosorbide, isomannide, and isoidet, which are stereoisomeric, and these may be used alone or in combination of two or more.

[0029] Among the dihydroxy compounds (A), isosorbide obtained by dehydration condensation of sorbitol produced from various starches, which are abundant and easily available as resources, is the most preferable from the viewpoints of availability and ease of production, optical properties, and moldability. In the present invention, isosorbide is preferably used as the dihydroxy compound (A).

[0030] (Dihydroxy Compound (B)) In the present invention, a dihydroxy compound (B) other than the dihydroxy compound (A) may be used as the dihydroxy compound. As the dihydroxy compound (B), for example, an alicyclic dihydroxy compound, an aliphatic dihydroxy compound, an oxyalkylene glycol, an aromatic dihydroxy compound, or a diol having a cyclic ether structure may be used as a dihydroxy compound serving as a structural unit of polycarbonate together with the dihydroxy compound (A), for example, a dihydroxy compound represented by formula (4).

[0031] The alicyclic dihydroxy compound usable in the present invention is not particularly limited, but preferably, a compound having a 5-membered ring structure or a 6-membered ring structure is used. The 6-membered ring structure may be fixed to a chair or boat shape by a covalent bond. The alicyclic dihydroxy compound has a 5-membered ring or a 6-membered ring structure, so that the heat resistance of the resulting polycarbonate can be increased. The number of carbon atoms contained in the alicyclic dihydroxy compound is usually 70 or less, preferably 50 or less, more preferably 30 or less. The larger this value, the higher the heat resistance, but the more difficult the synthesis, the more difficult the purification, and the higher the cost. The smaller the number of carbon atoms, the easier it is to purify and the easier it is to obtain.

[0032] Specific examples of the alicyclic dihydroxy compound containing a 5-membered ring structure or a 6-membered ring structure that can be used in the present invention include alicyclic dihydroxy compounds represented by the following general formula (II) or (III). HOCH2-R 1 -CH2OH (II) H.O.R. 2 -OH (III) (In formulas (II) and (III), R 1 , R 2 Each of the groups represents a cycloalkylene group having 4 to 20 carbon atoms. Cyclohexanedimethanol, which is an alicyclic dihydroxy compound represented by the above general formula (II), is a compound represented by the following general formula (II): 1 is represented by the following general formula (IIa) (wherein R 3 represents an alkyl group having 1 to 12 carbon atoms or a hydrogen atom. Specific examples of such isomers include 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol.

[0033] [ka]

[0034] The alicyclic dihydroxy compound represented by the above general formula (II), tricyclodecane dimethanol and pentacyclopentadecanedimethanol, are represented by the following general formula (II): 1 is represented by the following general formula (IIb) (wherein n is 0 or 1):

[0035] [ka]

[0036] The alicyclic dihydroxy compound represented by the above general formula (II), decalin dimethanol or tricyclotetradecane dimethanol, is a compound represented by the general formula (II), 1 These include various isomers represented by the following general formula (IIc) (wherein m is 0 or 1). Specific examples of such isomers include 2,6-decalin dimethanol, 1,5-decalin dimethanol, and 2,3-decalin dimethanol.

[0037] [ka]

[0038] Norbornane dimethanol, which is an alicyclic dihydroxy compound represented by the above general formula (II), is a compound represented by the following general formula (II): 1 The isomers include various isomers represented by the following general formula (IId): Specific examples of such isomers include 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, etc.

[0039] [ka]

[0040] Adamantane dimethanol, which is an alicyclic dihydroxy compound represented by the general formula (II), is 1is represented by the following general formula (IIe): Specific examples of such isomers include 1,3-adamantanedimethanol.

[0041] [ka]

[0042] In addition, cyclohexanediol, which is an alicyclic dihydroxy compound represented by the above general formula (III), is a compound represented by the following general formula (III): 2 is represented by the following general formula (IIIa) (wherein R 3 represents an alkyl group having 1 to 12 carbon atoms or a hydrogen atom. Specific examples of such isomers include 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, and 2-methyl-1,4-cyclohexanediol.

[0043] [ka]

[0044] The alicyclic dihydroxy compound represented by the above general formula (III), tricyclodecanediol and pentacyclopentadecanediol, are represented by the following general formula (III): 2 is represented by the following general formula (IIIb) (wherein n is 0 or 1):

[0045] [ka]

[0046] The alicyclic dihydroxy compound represented by the above general formula (III), decalindiol or tricyclotetradecanediol, is preferably a compound represented by the general formula (III), 2is represented by the following general formula (IIIc) (wherein m is 0 or 1). Specific examples of such isomers include 2,6-decalindiol, 1,5-decalindiol, and 2,3-decalindiol.

[0047] [ka]

[0048] The norbornanediol, which is an alicyclic dihydroxy compound represented by the above general formula (III), is a compound represented by the following general formula (III): 2 The isomers include various isomers represented by the following general formula (IIId): Specific examples of such isomers include 2,3-norbornanediol and 2,5-norbornanediol.

[0049] [ka]

[0050] The adamantanediol which is an alicyclic dihydroxy compound represented by the above general formula (III) is a compound represented by the following general formula (III): 2 The isomers include various isomers represented by the following general formula (IIIe): Specific examples of such isomers include 1,3-adamantanediol.

[0051] [ka]

[0052] Among the specific examples of the alicyclic dihydroxy compounds described above, cyclohexane dimethanols, tricyclodecane dimethanols, adamantane diols, and pentacyclopentadecanedimethanols are particularly preferred, and from the viewpoints of availability and ease of handling, 1,4-cyclohexane dimethanol, 1,3-cyclohexane dimethanol, 1,2-cyclohexane dimethanol, and tricyclodecane dimethanol are preferred. In the present invention, tricyclodecane dimethanol is preferably used as the dihydroxy compound (B).

[0053] Examples of the aliphatic dihydroxy compounds that can be used in the present invention include ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,5-heptanediol, and 1,6-hexanediol. Examples of the oxyalkylene glycols that can be used in the present invention include diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol.

[0054] Examples of aromatic dihydroxy compounds that can be used in the present invention include 2,2-bis(4-hydroxyphenyl)propane [=bisphenol A], 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxyphenyl)pentane, 2,4'-dihydroxy-diphenylmethane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-5-nitrophenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 3,3-bis(4-hydroxyphenyl)ethane, 4,4'-bis(4-hydroxyphenyl)ethane, 5,5'-bis(4-hydroxyphenyl)ethane, 6,5'-bis(4-hydroxyphenyl)ethane, 7,5'-bis(4-hydroxyphenyl)ethane, 8,5'-bis(4-hydroxyphenyl)ethane, 9,5'-bis(4-hydroxyphenyl)ethane, 10,5'-bis(4-hydroxyphenyl)ethane, 11,5'-bis(4-hydroxyphenyl)ethane, 12,5'-bis(4-hydroxyphenyl)ethane, 13,5'-bis(4-hydroxyphenyl)ethane, 14,5'-bis(4-hydroxyphenyl)ethane, 15,5'-bis(4-hydroxyphenyl)ethane, 16,5'-bis(4-hydroxyphenyl)ethane, 17,5'-bis(4-hydroxyphenyl)ethane, 18,5'-bis(4-hydroxyphenyl)ethane, 19,5'-bis(4-hydroxyphenyl)ethane, 20,5'-bis(4-hydroxyphenyl)ethane, 21,5'-bis(4-hydroxyphenyl)ethane, 22,5'-bis(4-hydroxyphenyl)ethane, 23, hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenyl sulfone, bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 4,4'-dihydroxy-2,5-diethoxydiphenyl ether, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-hydroxyethoxy-2-methyl)phenyl]fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-2-methylphenyl)fluorene.

[0055] Examples of the diols having a cyclic ether structure that can be used in the present invention include spiroglycols and dioxane glycols.The above-mentioned exemplary compounds are examples of the alicyclic dihydroxy compounds, aliphatic dihydroxy compounds, oxyalkylene glycols, aromatic dihydroxy compounds, and diols having a cyclic ether structure that can be used in the present invention, and are not limited thereto.One or more of these compounds can be used together with the dihydroxy compound represented by formula (4).

[0056] By using these dihydroxy compounds (B), it is possible to obtain effects such as improvement in flexibility, improvement in heat resistance, and improvement in moldability according to the application. The ratio of the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4), to the total dihydroxy compounds constituting the polycarbonate resin according to the present invention is not particularly limited, but is preferably 10 mol% or more, more preferably 40 mol% or more, even more preferably 60 mol% or more, preferably 90 mol% or less, more preferably 80 mol% or less, and even more preferably 70 mol% or less. If the content ratio of the structural unit derived from other dihydroxy compounds is too high, the performance such as optical properties may be deteriorated.

[0057] When an alicyclic dihydroxy compound is used among the other dihydroxy compounds, the proportion of the dihydroxy compound (A), for example the total proportion of the dihydroxy compound represented by formula (4) and the alicyclic dihydroxy compound, relative to all dihydroxy compounds constituting the polycarbonate is not particularly limited, but is preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more.

[0058] In addition, the content ratio of the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4) derived structural unit and the alicyclic dihydroxy compound derived structural unit in the polycarbonate resin according to the present invention can be selected at any ratio, but the structural unit derived from the dihydroxy compound represented by formula (4): the structural unit derived from the alicyclic dihydroxy compound = 1:99 to 99:1 (mol%) is preferable, and the structural unit derived from the dihydroxy compound represented by formula (4): the structural unit derived from the alicyclic dihydroxy compound = 10:90 to 90:10 (mol%) is particularly preferable. If the structural unit derived from the dihydroxy compound represented by formula (4) is more and the structural unit derived from the alicyclic dihydroxy compound is less than the above range, the coloring is likely to occur, and conversely, if the structural unit derived from the dihydroxy compound represented by formula (4) is less and the structural unit derived from the alicyclic dihydroxy compound is more, the molecular weight tends to be difficult to increase.

[0059] Furthermore, when an aliphatic dihydroxy compound, an oxyalkylene glycol, an aromatic dihydroxy compound, or a diol having a cyclic ether structure is used, the total ratio of the dihydroxy compound (A), for example, the dihydroxy compound represented by formula (4), and each of these dihydroxy compounds to the total dihydroxy compounds constituting the polycarbonate is not particularly limited and can be selected at any ratio. In addition, the content ratio of the dihydroxy compound (A), for example, the constituent unit derived from the dihydroxy compound represented by formula (4), and each of these dihydroxy compounds is not particularly limited and can be selected at any ratio.

[0060] Details of polycarbonate-based resins are described, for example, in JP 2012-31370 A (Patent No. 5448264), the disclosure of which is incorporated herein by reference.

[0061] C. Method for manufacturing retardation film The method for producing a retardation film according to the embodiment of the present invention includes stretching a resin film. The resin film is a film formed from the polycarbonate resin described in the above section B.

[0062] In one embodiment, the retardation film may be produced by biaxial stretching. The biaxial stretching may be simultaneous biaxial stretching or sequential biaxial stretching. The stretching ratio in the longitudinal direction is preferably more than 1.0 times and not more than 2.0 times, more preferably 1.1 times to 1.5 times. The stretching ratio in the transverse direction is preferably 1.6 times to 2.2 times, more preferably 1.8 times to 2.0 times. By stretching the film formed from the above polycarbonate resin at such a stretching ratio, it is possible to realize not only desired optical properties but also very excellent mechanical properties (for example, bending property, sebum resistance, crack resistance).

[0063] The stretching temperature of the resin film is preferably Tg-30°C to Tg+30°C, more preferably Tg-15°C to Tg+15°C, and further preferably Tg-10°C to Tg+10°C. By stretching at such a temperature, a retardation film having suitable properties in the present invention can be obtained. Note that Tg is the glass transition temperature of the constituent material of the film.

[0064] D. Polarizing plate with retardation layer The retardation film according to any one of A to C above may be provided as a laminate with another retardation film and / or an optical member. In one embodiment, the retardation film may be provided as a laminate with a polarizing plate (typically, a polarizing plate with a retardation layer). Thus, the present invention encompasses a polarizing plate with a retardation layer having the above retardation film. In the retardation film, the angle between the absorption axis of the polarizer of the polarizing plate and the slow axis of the retardation film may be appropriately set depending on the application and purpose. In one embodiment, the angle is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°.

[0065] The polarizing plate with a retardation layer typically has a polarizer and the above-mentioned retardation film attached to at least one surface of the polarizer via an adhesive layer. The polarizer may have a protective layer on at least one surface of the polarizer. Furthermore, the polarizing plate may have a pressure-sensitive adhesive layer and a separator on the surface opposite to the viewing side.

[0066] Any appropriate polarizer can be used as the polarizer. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.

[0067] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.

[0068] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.

[0069] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. Details of the manufacturing method of such polarizers are described in, for example, JP 2012-73580 A (Patent No. 5414738 A). The description of this patent document is incorporated herein by reference. The entire description of this publication is incorporated herein by reference.

[0070] In one embodiment, the thickness of the polarizer is preferably 1 μm to 25 μm, more preferably 3 μm to 10 μm, and further preferably 3 μm to 8 μm. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.

[0071] The protective layer is formed of any suitable protective film that can be used as a film for protecting a polarizer. Specific examples of materials that are the main components of the protective film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, polynorbornene-based, polyolefin-based, (meth)acrylic-based, acetate-based, and other transparent resins. In addition, examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylic-based, urethane-based, (meth)acrylic urethane-based, epoxy-based, and silicone-based resins. In addition, examples include glassy polymers such as siloxane-based polymers. In addition, the polymer films described in JP-A-2001-343529 (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.

[0072] The thickness of the protective layer is preferably 10 μm to 100 μm. The protective layer may be laminated on the polarizer via an adhesive layer (specifically, an adhesive layer, a pressure-sensitive adhesive layer), or may be laminated in close contact with the polarizer (without an adhesive layer). If necessary, a surface treatment layer such as a hard coat layer, an antiglare layer, and an antireflection layer may be formed on the protective layer disposed on the outermost surface of the retardation layer-attached polarizing plate.

[0073] The retardation layer-attached polarizing plate can be used on the viewing side of an image display device. Furthermore, the retardation layer in the retardation layer-attached polarizing plate may be disposed on the viewing side or on the display cell side.

[0074] Any suitable adhesive may be used as the adhesive forming the adhesive layer. Examples of the base resin of the adhesive include acrylic resin, styrene resin, silicone resin, urethane resin, and rubber resin. Such base resins are described in, for example, JP 2015-120337 A (Patent No. 6457789) or JP 2011-201983 A. The descriptions in these publications are incorporated herein by reference. Examples of crosslinking agents that may be included in the adhesive include isocyanate compounds, epoxy compounds, and aziridine compounds. The adhesive may include, for example, a silane coupling agent. The formulation of the adhesive may be appropriately set according to the purpose and desired properties.

[0075] The storage modulus of the adhesive layer is preferably 1.0×10 4 Pa~1.0×10 7 Pa, more preferably 2.0×10 4 Pa~5.0×10 6 The storage modulus is Pa. If the pressure-sensitive adhesive layer has a storage modulus in this range, blocking during roll formation can be suppressed. The storage modulus can be determined, for example, by dynamic viscoelasticity measurement at a temperature of 23° C. and an angular velocity of 0.1 rad / s.

[0076] The thickness of the adhesive layer is preferably 1 μm to 60 μm, and more preferably 3 μm to 30 μm. If the thickness is too thin, the adhesiveness becomes insufficient and air bubbles may get into the adhesive interface. If the thickness is too thick, problems such as the adhesive protruding out are likely to occur.

[0077] For practical purposes, a separator is temporarily attached to the surface of the adhesive layer in a peelable manner until the retardation film is actually used. Examples of the separator include plastic (e.g., polyethylene terephthalate (PET), polyethylene, polypropylene) films, nonwoven fabrics, and papers, the surfaces of which are coated with a release agent such as a silicone-based release agent, a fluorine-based release agent, or a long-chain alkyl acrylate-based release agent. The thickness of the separator can be any appropriate thickness depending on the purpose. The thickness of the separator is, for example, 10 μm to 100 μm. EXAMPLES

[0078] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring and evaluating each property are as follows. (1) In-plane retardation and wavelength dispersion characteristics The retardation films obtained in the examples and comparative examples were cut into a length of 4 cm and a width of 4 cm to be used as measurement samples. The in-plane retardation Re(550) of the measurement samples was measured using an Axoscan manufactured by Axometrics. Furthermore, Re(450) was also measured, and Re(450) / Re(550) was calculated. (2) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (3) Moisture permeability The retardation films obtained in the examples and comparative examples were subjected to a moisture permeability test (cup method) according to JIS Z0208 in an atmosphere at a temperature of 40°C and a humidity of 92% RH, with an area of ​​1 m 2 The amount of water vapor (g) passing through the sample in 24 hours was measured. (4) Phase difference change The retardation films obtained in the examples and comparative examples were cut into 5 cm x 5 cm pieces, adhesive was applied to one side of the pieces with a hand roller, and the adhesive side was applied to one side of an alkaline glass to obtain a test piece. The test piece was stored in an oven at a temperature of 65°C and a humidity of 90% for 500 hours (humidification test), and the change in retardation (%) before and after the test was calculated. (5) Phase difference variation Similarly to (1), the in-plane retardation Re(550) of the retardation films obtained in the examples and comparative examples was measured. Nine points were measured in the width direction of the retardation film, and the difference between the maximum and minimum retardation values ​​was taken as the retardation variation. (6) Puncture elastic modulus The piercing elastic modulus was obtained by dividing the force (gf) just before the retardation film in the Examples and Comparative Examples breaks (or tears) when a needle (piercing tool) is pierced perpendicularly to the main surface of the retardation film by the strain (mm) at that time. The needle used had a tip diameter of 1 mmφ and 0.5R. The needle piercing speed was 0.33 cm / sec. The measurement was performed in an environment at a temperature of 23°C. (7)Puncture strength A tester equipped with a needle with a tip diameter of 1 mmφ and 0.5R was used. The retardation film was sandwiched between two jigs with a circular hole in the center, and the retardation film was fixed to the tester. The needle was vertically lowered onto the retardation film so as to pass through the hole in the jig, and the strength when the retardation film was broken was measured. The test conditions were an environment of a temperature of 23±3°C and a piercing speed of 0.33 cm / sec. A piercing test was performed on 12 test pieces, and the average value was divided by the thickness of the retardation film to determine the piercing strength per unit film thickness of the retardation film. (8) Breaking strength and breaking elongation The retardation films obtained in the examples and comparative examples were cut to a width of 1 cm and a length of 13 cm, and then a tensile test was performed using an Autograph ASG-50D (manufactured by Shimadzu Corporation) at a tensile speed of 200 mm / min, a chuck distance of 50 mm, and room temperature (23°C). The stress at which the retardation film broke was calculated as the breaking strength, and the strain (elongation rate) at which the retardation film broke was calculated as the breaking strength. (9) Adhesiveness The retardation film and the polarizer obtained in the examples and comparative examples were laminated together to obtain a laminate. The obtained laminate was cut into a size of 200 mm parallel to the stretching direction of the polarizer and 15 mm in the perpendicular direction, and the laminate was laminated to a glass plate. Then, a cut was made between the retardation film and the polarizer with a cutter knife, and the retardation film and the polarizer were peeled off in the 90° direction at a peeling speed of 1000 mm / min using a Tensilon universal testing machine RTC (manufactured by A&D Co., Ltd.), and the peel strength (N / 15 mm) was measured. A peel strength of 1 N / 15 mm or more was considered good, and a peel strength of less than 1 N / 15 mm was considered bad. (10) Runnability (evaluation of process defects during transportation) The retardation films obtained in the examples and comparative examples were rated as good if they did not suffer from defects such as bends, scratches, dents, etc. (if they could be transported without problems) when transported at a speed of 5 m / min to 40 m / min using guide rolls, and rated as bad if they suffered from bends, scratches, dents, etc. (11) Flexibility (MIT test) The MIT test was carried out in accordance with JIS P 8115. Specifically, the retardation films obtained in the examples and comparative examples were cut into a length of 15 cm and a width of 1.5 cm to be used as measurement samples. The measurement sample was attached to an MIT folding fatigue tester BE-202 type (manufactured by Tester Sangyo Co., Ltd.) (load 1.0 kgf, clamp R: 0.38 mm), and repeatedly folded at a test speed of 90 cpm and a folding angle of 90°, and the number of foldings at which the measurement sample broke was used as the test value. A value of 500 or more was considered good, and a value of less than 500 was considered bad. (12) Evaluation of bright spots during indentation A sample similar to the sample evaluated in the piercing strength test was attached to a polarizer, and the film side was pressed with a force of 10 gf / μm using a piercing tester. Then, a polarizing plate was prepared so that it formed an axis of 90° with the polarizing plate, and in a crossed Nicol state, transmitted light was transmitted from the opposite side of the film that had been pierced and the sample was rated as good if no bright spots were observed, and as bad if bright spots were observed. (13) Sebum resistance The retardation films obtained in the examples and comparative examples were cut into 5 cm x 5 cm pieces, adhesive was applied to one side of the pieces using a hand roller, and the adhesive side was applied to one side of an alkaline glass to obtain a test piece. The obtained test pieces were immersed in an oleic acid solution at 65°C and 90% RH for 72 hours, and after removal, those that were transparent were rated as good, and those that were whitened or cracked were rated as bad. (14) Crack resistance The retardation films obtained in the examples and comparative examples were subjected to a heat shock test from -40°C to 80°C for 300 cycles, and the films were rated as good if no cracks of 300 μm or more were generated, and as poor if cracks of 300 μm or more were generated.

[0079] [Example 1] 1. Preparation of resin film 81.98 parts by mass of isosorbide (hereinafter sometimes abbreviated as "ISB"), 47.19 parts by mass of tricyclodecane dimethanol (hereinafter sometimes abbreviated as "TCDDM"), 175.1 parts by mass of diphenyl carbonate (hereinafter sometimes abbreviated as "DPC"), and 0.979 parts by mass of cesium carbonate 0.2% by mass aqueous solution as a catalyst were charged into a reaction vessel, and in a nitrogen atmosphere, as the first step of the reaction, the heating tank temperature was heated to 150°C and the raw materials were dissolved while stirring as necessary (about 15 minutes). Next, the pressure was changed from normal pressure to 13.3 kPa, and the heating tank temperature was increased to 190°C over one hour, while the generated phenol was extracted from the reaction vessel. After the entire reaction vessel was kept at 190°C for 15 minutes, the pressure in the reaction vessel was set to 6.67 kPa, the heating tank temperature was raised to 230°C in 15 minutes, and the generated phenol was extracted outside the reaction vessel as the second step. As the stirring torque of the stirrer increased, the temperature was raised to 250°C in 8 minutes, and the pressure in the reaction vessel was allowed to reach 0.200 kPa or less in order to remove the further generated phenol. After reaching a predetermined stirring torque, the reaction was terminated, and the reaction product was extruded into water to obtain polycarbonate resin pellets. The obtained polycarbonate resin was vacuum-dried at 80°C for 5 hours, and then a polycarbonate resin film having a thickness of 90 μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 300 mm, setting temperature: 250°C), a chill roll (setting temperature: 120 to 130°C), and a winder.

[0080] 2. Preparation of Retardation Film The unstretched polycarbonate resin film was subjected to a preheating treatment and simultaneous biaxial stretching using a simultaneous biaxial stretching machine to obtain a retardation film. The preheating temperature was 133°C, the stretching temperature was 135°C, the stretching ratio in the longitudinal direction was 1.2 times, and the stretching ratio in the transverse direction was 1.9 times. The wavelength dispersion value of the obtained retardation film was 1.025, the in-plane retardation Re(550) was 269 nm, the thickness was 40 μm, and the moisture permeability was 80 g / m 224h, the change in retardation was 0.8%, and the variation in in-plane retardation was 2 nm. Furthermore, the retardation film had a puncture modulus of 375 gf / mm, a puncture strength of 24 gf / μm, a breaking strength of 2530 MPa, and a breaking elongation of 5.6%. The obtained retardation film was subjected to the above evaluations (9) to (14). The results are shown in Table 1.

[0081] [Example 2] A retardation film was obtained in the same manner as in Example 1, except that the preheating temperature was 133° C., the stretching temperature was 135° C., the stretching ratio in the longitudinal direction was 1.2 times, and the stretching ratio in the transverse direction was 1.9 times. The wavelength dispersion value of the obtained retardation film was 1.021, the in-plane retardation Re(550) was 271 nm, the thickness was 40 μm, and the moisture permeability was 97 g / m 2 24h, the change in retardation was 1%, and the variation in in-plane retardation was 2nm. Furthermore, the retardation film had a puncture modulus of 386gf / mm, a puncture strength of 24gf / μm, a breaking strength of 2530MPa, and a breaking elongation of 5.6%. The obtained retardation film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0082] [Example 3] A retardation film was obtained in the same manner as in Example 1, except that the preheating temperature was 133° C., the stretching temperature was 135° C., the stretching ratio in the longitudinal direction was 1.2 times, and the stretching ratio in the transverse direction was 1.9 times. The wavelength dispersion value of the obtained retardation film was 1.025, the in-plane retardation Re(550) was 300 nm, the thickness was 40 μm, and the moisture permeability was 76 g / m 2 24h, the change in retardation was 0.8%, and the variation in in-plane retardation was 2 nm. Furthermore, the retardation film had a puncture modulus of 398 gf / mm, a puncture strength of 23 gf / μm, a breaking strength of 2530 MPa, and a breaking elongation of 5.6%. The obtained retardation film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0083] [Comparative Example 1] The rotation axis of the rubbing roller was adjusted to 45° counterclockwise with respect to the longitudinal direction of a triacetyl cellulose (TAC) film (manufactured by Fuji Film Corporation), and rubbing treatment was performed. A liquid crystal was coated on the rubbed TAC film to obtain a liquid crystal-coated triacetyl cellulose (TAC) film. A retardation film was obtained in the same manner as in Example 1, except that this liquid crystal-coated TAC film was used as the resin film and stretching was not performed. The wavelength dispersion value of the obtained retardation film was 1.09, the in-plane retardation Re(550) was 260 nm, the thickness was 2 μm, and the moisture permeability was 330 g / m 2 24h, the retardation change was 4%, and the variation in the in-plane retardation was 1 nm. Furthermore, the retardation film had a puncture modulus of 20gf / mm, a puncture strength of 5gf / μm, a breaking strength of 250MPa, and a breaking elongation of 3.8%. The obtained retardation film was subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0084] [Table 1]

[0085] As is clear from Table 1, the retardation films of the examples of the present invention are excellent in all of adhesion, running property, bending property, suppression of bright spots when pressed, sebum resistance, and crack resistance. This is presumably achieved by using a retardation film containing a specific polycarbonate resin, and by setting the puncture modulus, puncture strength per unit film thickness, breaking strength, and breaking elongation of the retardation film all within specific ranges. [Industrial Applicability]

[0086] The retardation film according to the embodiment of the present invention is suitably used in notebook PCs, in-vehicle displays, and the like.

Claims

1. A retardation film comprising a polycarbonate resin, having an in-plane retardation Re(550) of 200 nm to 400 nm, a thickness of 30 μm to 50 μm, Re(450) / Re(550) of 0.98 to 1.03, and a puncture modulus of 375 gf / mm or more.

2. The retardation film according to claim 1 , which has a puncture strength per unit thickness of 10 gf / μm or more.

3. The retardation film according to claim 1 or 2, having a breaking strength of 800 MPa or more.

4. 4. The retardation film according to claim 1, wherein the variation in Re(550) in the width direction is 5 nm or less.

5. 5. The retardation film according to claim 1, wherein an absolute value of a rate of change in in-plane retardation Re(550) after 500 hours under conditions of a temperature of 65° C. and a humidity of 90% is 3% or less.

6. Moisture permeability is 150g / m 2 The retardation film according to any one of claims 1 to 5, which has a retardation time of 24 hours or less.

7. The retardation film according to claim 1 , which has a breaking elongation of 4% or more.

8. 8. A polarizing plate with a retardation layer, comprising: a polarizer; and the retardation film according to claim 1 attached to at least one surface of the polarizer via an adhesive layer.

Citation Information

Patent Citations

  • Polarizing plate and display device

    JP2019185007A

  • Retardation film and optical device using the same

    JP3325560B2

  • Polycarbonate resin and optical film using the same

    WO2008020636A1